Aktivitas Antibakteri Daun Mangga (Mangifera Indica L) Terhadap Bakteri Pada Sputum - Dini Fatwa Tri Utami; Muthia Zahra; Siti Fathia Azhar Hasibuan; Yazima Fadila Ningsih (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
Mango (Mangifera indica L.) is a native plant from Southeast Asia, and has been widely distributed in tropical and subtropical regions of the world. Mango leaf extract is reported to contain alkaloids, phenols, saponins, coumarins, tannins, flavonoids, triterponoids, steroids and glycosides which function as antimicrobial compounds that can inhibit bacterial growth. It is hoped that this content can be a solution as an antibacterial to replace antibiotics, because inappropriate use of antibiotics can cause bacteria to become resistant. The aim of this study was to test the antibacterial activity of mango leaves against bacteria from sputum samples. The extraction method used was infusion with paper discs on Mueller Hinton Agar (MHA) medium which was incubated at 37°C for 24 hours. The positive control used was the antibiotic Amoxicillin